Tropical soils with high aluminum concentrations cause oxidative stress in two tomato genotypes - Nogueirol, Roberta Correa; Monteiro, Francisco Antonio; Gratao, Priscila Lupino [UNESP]; Borgo, Lucelia; Azevedo, Ricardo Antunes (Springer, 2015)
Tropical and subtropical soils are usually acidic and have high concentrations of aluminum (Al). Aluminum toxicity in plants is caused by the high affinity of the Al cation for cell walls, membranes, and metabolites. In this study, the response of the antioxidant-enzymatic system to Al was examined in two tomato genotypes: Solanum lycopersicum var. esculentum (Calabash Rouge) and Solanum lycopersicum var. cerasiforme (CNPH 0082) grown in tropical soils with varying levels of Al. Plant growth; activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPOX), and glutathione reductase (GR) enzymes; stress-indicating compounds (malondialdehyde (MDA) and hydrogen peroxide); and morphology (root length and surface area) were analyzed. Increased levels of Al in soils were correlated with reduced shoot and root biomass and with reduced root length and surface area. Calabash Rouge exhibited low Al concentrations and increased growth in soils with the highest levels of Al. Plants grown in soils with high availability of Al exhibited higher levels of stress indicators (MDA and hydrogen peroxide) and higher enzyme activity (CAT, APX, GPOX, and GR). Calabash Rouge absorbed less Al from soils than CNPH 0082, which suggests that the genotype may possess mechanisms for Al tolerance.
Keywords: Soil acidity; Toxic element; Aluminum; Antioxidant enzymes; Weathered soils